1970
DOI: 10.1159/000259628
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fluoride Concentration and the Caries Frequency of Different Tooth Surfaces in a High Fluoride Area

Abstract: A clinical investigation on caries attack of different dental surfaces was carried out in a high fluoride area (Campagnano) in 144 adults. At the same time the fluoride concentration of 269 samples of different dental surfaces of 65 caries-free teeth, belonging to adults from the same area, was determined. Statistical analysis of clinical and chemical data, and a comparison between these data and earlier data collected in a low fluoride area (Rieti) were carried out. Highly significant differences, both in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…This finding is consistent with the different fluoride content in each surface type (i.e. occlusal vs. smooth) [Candeli et al, 1970] and has been replicated in experimental studies of both fluoride mouthrinses [Ripa et al, 1985] and varnishes [Koch and Petersson, 1975]. However, evidence is lacking with regard to the caries-preventive efficacy of FV among different types of primary teeth, based either on tooth anatomy or existing pathology.…”
supporting
confidence: 79%
“…This finding is consistent with the different fluoride content in each surface type (i.e. occlusal vs. smooth) [Candeli et al, 1970] and has been replicated in experimental studies of both fluoride mouthrinses [Ripa et al, 1985] and varnishes [Koch and Petersson, 1975]. However, evidence is lacking with regard to the caries-preventive efficacy of FV among different types of primary teeth, based either on tooth anatomy or existing pathology.…”
supporting
confidence: 79%
“…N01-DE-12432. dalia et al, 1961;Candeli et al, 1970;De Paola et al, 1975;Bischoff et al, 1976;Keene et al, 1975;Englander and Mell berg, 1976;Poulsen and Larsen, 1975;Van der Merwe et al, 1977;Richards et al, 1977], Schamschula et al [1979] suggested that surface fluoride changes due to wear, pre vious caries challenge, or topical fluoride exposure might mask the true effect within a community, and in a small sample (n = 36) he found a significant correlation be tween caries and fluoride levels at enamel depths greater than 4 urn.…”
mentioning
confidence: 98%
“…In several of these studies no significant correlation could be established between dental caries experience and enamel F concentration [Candeli et al, 1970;Keene et al, 1975;Poulsen and Larsen, 1975;Bischoff et al, 1976;Richards et al, 1977;Van der Merwe et al, 1977;Retief et al, 1979a;Nasir et al, 1985]. In another study no significant association between the F concentration in surface enamel and den tal caries was obtained but significant in verse correlations between DM FT and the F concentrations in the subsurface enamel layers were recorded [Schamschula et al, 1979).…”
mentioning
confidence: 98%